Book Reviews - Judy Halden-Sullivan; Lauren DiPaula; William Archibald; Noam Scheindlin; Martin Cockroft (Journal of the Assembly for Expanded Perspectives on Learning, 2012)
Book Reviews Judy Halden-Sullivan - Paradigm Shifts Lauren DiPaula - Price, Margaret. Mad At School: Rhetorics of Mental Disability and Academic Life. Ann Arbor: University of Michigan Press, 2011. William Archibald - Thomas, Douglas and John Seely Brown. A New Culture of Learning: Cultivating the Imagination for a World of Constant Change. Charleston, SC: CreateSpace, 2011. Noam Scheindlin - Vandermeulen, Carl. Negotiating the Personal in Creative Writing. Bristol: Multilingual Matters, 2011. Martin Cockroft - Wilhelm, Jeffrey D. and Bruce Novak. Teaching Literacy for Love and Wisdom: Being the Book and Being the Change. NY: Teachers College Press, 2011.